ASSESSMENT OF ACCURACY AND PRECISION STATISTICS IN ROUTINE BIOCHEMISTRY AUTOANALYZER USING INTERNAL QUALITY CONTROL SPECIMENS IN A TERTIARY CARE HOSPITAL LABORATORY - Bhattarai , Kushal; Joshi , Bishal Raj; Shrestha , Dojindra (Journal of Chitwan Medical College, 2022)
Background: Accuracy and precision are two important yardsticks of a reliable analytical system in the clinical laboratory. The study was designed to determine the accuracy and precision statistics of a routine biochemistry auto-analyzer using two levels of quality control materials and to compare these statistics with the company provided values. The study also aimed to compare the month-wise variations in these statistics. Methods: It was a cross-sectional study conducted in the Department of Biochemistry at Birat Medical College Teaching Hospital, Nepal. Laboratory data for the months of May–July, 2021 were retrieved from the laboratory information system (LIS). The retrieved data comprised of the results of two levels of quality control specimens run routinely on Beckman Coulter AU480 biochemistry autoanalyzer for most of the biochemical parameters. Accuracy and precision statistics were calculated as mean and coefficient of variation, respectively. Results: In both levels of control samples, the laboratory determined accuracy statistics were greater in magnitude than the company provided ones for albumin, alkaline phosphatase, aspartate transaminase, creatinine, unsaturated iron binding capacity, urea, direct bilirubin, and amylase; the precision statistics were similarly greater in magnitude for total protein and magnesium. In month-wise comparison of laboratory determined accuracy statistics, the overall mean differences were statistically significant (p<0.05) for all parameters except lactate dehydrogenase and magnesium (both levels of control). Conclusions: The laboratory determined accuracy and precision statistics showed variations from the company provided ones apart from the month-wise variation. Therefore, continuous monitoring of these values is mandatory for ensuring reliable test reports.